ELECTRONIC ARCHIVES MANAGEMENT: A DESCRIPTIVE ANALYSIS TOWARDS THE QUALITY IMPROVEMENT OF HIGHER EDUCATION ACCREDITATION AT UIN SULTAN MAULANA HASANUDDIN BANTEN - Nurmaita Hamsyiah; Umiyati Umiyati; Husnul Amalia Safitri (Unversitas Muhammadiyah Mataram, 2024)
This research is aimed at providing an overview of electronic archives management at UIN Sultan Maulana Hasanuddin Banten and comparing it to existing standard in Indonesia, and analyzing problems found in electronic archives management and presenting alternative solutions in an effort to improve the quality of higher education accreditation at UIN Sultan Maulana Hasanuddin Banten. This descriptive research uses qualitative approach. Data collecting techniques are carried out using observation, interview, and documentation. Data is obtained from 9 informants, including 4 archivists and 5 archive users. The data analysis techniques include data reduction, data display, and conclusions drawing. This research result shows that UIN Sultan Maulana Hasanuddin Banten has not had a centralized electronic archives management system yet so there is a gap with the electronic archives standards set in Indonesia. Archivist competency, facilities and infrastructure, as well as internet networks and application systems are problems that occur at UIN Sultan Maulana Hasanuddin Banten. Therefore, it is necessary to train and develop archivists, provide facilities and infrastructure, and upgrade security systems, both networks and applications. Keyword:Information TechnologyElectronic ArchivesANRI